IMPROVING COMPETITIVENESS THROUGH MAKING SIMPLE CASH BOOKS FOR BUSINESS TAILOR AND MIE REBUS / SATE - Nurzaimah; Ismail, Mutia; Indra, Naleni (Talenta Publisher, 2018)
Devotion is done in Medan City and Lubuk Pakam,Sumatera Utara Province. Devotion takes the title